Beihaghi’s View of the ShortReign of Amir Muhammad... - Ghasem Sahraee (مجله مطالعات ایرانی, 2016)
The short-term reign of Amir Mohammad, the son of Sultan Mahmoud Ghaznavi, in 421 AH, is a rarely-discussed question. Historians and researchers have briefly dealt with this issue; however, since Beihaghi’s History fairly presents the grounds and reasons for coming of Mohammad to the throne, it can serve as an authoritative reference for the present study. Through a descriptive-analytical method, the question of Mohammad’s throne and his dethronement are discussed here. The results show that Sultan Mahmoud’s resentment toward Masoud, and his efforts were the main reasons for Mohammad’s coming to throne, and that issues such as lack of Mahmoud’s sovereignty, the King’s lack of competency, Masoud’s valor, and the provocation of and bribing the aristocrats by Masoud are among the main factors for Mohammad’s dethronement.